Estudio del Patrimonio inmaterial del ámbito 3: usos Sociales, Rituales y Actos Festivos; sub ámbito: Fiestas Religiosas de la Parroquia Mulaló, Cantón Latacunga - Caiza Llano, Jennifer Belén (2018)
The Intangible Heritage Study of ambit 3: social usages, rituals, and festive acts; sub ambit: religious celebrations in Mulalo parish, has a huge importance to the research place, where an inventory analysis was done about religious celebrations which take place into parish’s neighborhoods and communities. To raise initial information a situational diagnosis got carried out through interviews and bibliographic review. After the diagnosis, an inventory was done about the religious commemorations that take place in the parish, where the number of festivities existing in the site was known, for the inventory the INPC (National Institute of Cultural Heritage) record methodologies was applied. As a result it was obtained that the parish has 12 celebrations, which are carried out in an eight-month timeline, distributed on different dates throughout the year. Finally, with the compilation of information, a guide was drawn up, which covers various cultural manifestations recorded during the field work. For the designing of the same it was necessary to systematize the inventory information and the interviews conducted, obtaining key data for its execution. The development of the guide is considered as an instrument of dissemination and promotion, where readers can learn about the historical richness of the festivities.